The optimal spending rate versus the expected real return of a sovereign wealth fund - Knut K. Aase; Petter Bjerksund (Journal of Risk and Financial Management, 2021)
We consider a sovereign wealth fund that invests broadly in the international financial markets. The influx to the fund has stopped. We adopt the life cycle model and demonstrate that the optimal spending rate from the fund is significantly less than the fund's expected real rate of return. The optimal spending rate ensures that the fund will last "forever". Spending the expected return will deplete the fund with probability one. Moreover, this strategy is inconsistent with optimal portfolio choice. Our results are contrary to the idea that it is sustainable to spend the expected return of a sovereign wealth fund.
Keywords: G10; G12; D9; D51; D53; D90; E21; 330; EIS; endowment funds; expected utility; optimal spending rate; recursive utility; risk aversion